International press coverage of Peruvian’s presidential election in 2021 - Arce Ortiz, Natalia Verónica (2022)
This research paper analyzes the Bolivian media coverage of the presidential runoff of the 2021 General Elections in Peru, in which the candidates participated: Pedro Castillo and Keiko Fujimori. The main objective was to study the frames that El Diario and La Razón used in the journalistic articles of their web portals. Likewise, we identified the digital space given to the publications and recognized the profiles that the foreign press built around each candidate. From a mixed approach, we analyzed metrics and used qualitative tools to examine the use of level and generic framing. To do so, we focused on the media with the highest readership in La Paz and analyzed 34 web articles that were published between April 12 and June 6, 2021. The results show that 44% were journalistic products lacking depth in which less than 400 words were used; 35% presented confrontational frames; 43% referred to Castillo as "rural teacher", while 38% of publications labeled Keiko Fujimori as "the daughter of the imprisoned". Finally, the researchers concluded that there is an informative hegemony on the part of international agencies in the electoral processes. This is evidence of a lack of interest on the part of the Bolivian media in the journalistic coverage of political events in a neighboring country.